Effectiveness of stretching exercise to reduce muscle cramps in patients with pulmonary edema - Soumya, K.; V. Sheeja, C.; M. Assuma Beevi, T. (International Journal of Nursing Research, 2023)
Introduction: Patients with pulmonary edema are restricted to bed and usually are very weak. When such patients are experiencing leg cramps, strategies such as walking or warm shower are impracticable. Stretching exercises are known strategies used for relieving muscular strain and muscle spasm. Objectives: The objectives of the study were to assess the intensity and frequency of muscle cramps in patients with pulmonary edema and to evaluate the effectiveness of stretching exercise on muscle cramps. Materials and Methods: Quantitative research approach with pre-experimental one group pre-test post-test design on 30 patients with pulmonary edema who had muscle cramps > 5 was selected purposively. Data were collected using demographic pro forma, clinical pro forma, modified PSFS scale, and numerical pain intensity scale. Muscle stretching exercise was given for duration of 10 min 8th hourly for 3 times. Intensity of muscle cramp was assessed immediately after the first intervention and the frequency of muscle cramp was reassessed 8 h after third intervention. Results: The muscle cramp intensity showed a total of 100% had severe pain before the intervention. About 73.3% had mild and 26.7% had moderate intensity after the intervention. The paired “‘t” value was 2.05 with P = 0.001 which was highly significant at 0.05 level after undergoing stretching exercise. Conclusion: The findings concluded that stretching exercise was effective in reducing the muscle cramp. Patients in ICUs are experiencing pain and cramp. Simple and cost effective exercises will be useful in reducing pain and improve the quality of nursing care.